Polyethylene glycol fusion associated with antioxidants: A new promise in the treatment of traumatic facial paralysis. Issue 7 (9th March 2018) - Salomone, Raquel; Jácomo, Alfredo Luiz; Nascimento, Silvia Bona do; Lezirovitz, Karina; Hojaij, Flávio Carneiro; Costa, Heloisa Juliana Zabeu Rossi; Bento, Ricardo Ferreira
Abstract: Background: Recent studies in invertebrates have taught us that early cell membrane regeneration is determinant for axonal recovery and survival after trauma. Many authors obtained extraordinary results in neural regeneration using polyethylene glycol fusion protocols, which also involved microsutures and antioxidants. Methods: Sixty rats were evaluated with functional and histological protocol after facial nerve neurotmesis. Groups A and B had their stumps coapted with microsuture after 24 hours of neurotmesis and groups C and D after 72 hours. In addition to the microstructure, groups B and D used the polyethylene glycol‐fusion protocol for the modulation of the Ca +2 . Results: At the sixth week, the latency of group D and duration of group B was lower than groups A and C ( P = .011). The axonal diameter of the groups that used polyethylene glycol‐fusion was higher than those who did not use polyethylene glycol‐fusion ( P ≤ .001). Conclusion: Although not providing a functional improvement, polyethylene glycol‐fusion slowed down demyelination.